Additive-treated corn silage, harvestore cornlage, and sodium bicarbonate supplement for yearling steers - Soderlund, S.; Bolsen, K.; Ilg, H.; Hoover, J. (Kansas State University. Agricultural Experiment Station, 2010)
Steers fed Silo Guard II® treated corn silage gained 3.5% faster and were 8.3% more efficient than those fed the control silage. Cornlage (54% dry matter corn silage in an oxygen-limiting structure) produced numerically slower and less efficient gains than either treated or untreated silage, but differences in silages were not statistically significant. Steers fed sodium bicarbonate throughout the trial consumed 8.5% more silage, gained 14% faster (P<.05), and were 3% more efficient than those not fed bicarbonate; performance of steer fed bicarbonate for the first half of the trial was intermediate. Steers fed cornlage had a higher rumen fluid acetate:propionate ratio (P<.05) than those fed the control or Silo Guard II silages but there were no significant differences due to bicarbonate in rumen fluid volatile fatty acids. Silage DM recoveries and aerobic stabilities were similar for the control and Silo Guard II silages. Cornlage was less stable in air than the other two silages.
Keywords: Beef; Corn silage; Cornlage; Sodium bicarbonate; Steers